Nb-V-enriched sövites of the northeastern and eastern part of the Amba Dongar carbonatite ring dike, India: a reflection of post-emplacement hydrothermal overprint? - Magna, Tomáš; Viladkar, Shrinivas; Rapprich, Vladislav; Pour, Ondrej; Hopp, Jens; Cejkova, Bohuslava (Geochemistry, 2020)
Wakefieldite-(Ce,La) and vanadinite in coarse-grained calciocarbonatites (sovites) are for the first time reported from the northeastern part of the worldwide largest fluorite deposit at the Amba Dongar carbonatite ring dike, India. Sovite in this part of the carbonatite ring dike is rich in pyrochlore, calcite and magnetite. Pyrochlore makes up almost 50% of some sovite samples and shows core-to-rim compositional changes. The core of pyrochlore consists of primary fluorcalciopyrochlore with high F and Na contents while the margins gained elevated amounts of Pb, La and Ce with the associated loss of F and Na due to circulation of hydrothermal solutions. The presence of wakefieldite-(Ce,La) and vanadinite points to an exceptionally high V abundance in hydrothermal solutions formed towards the end of the carbonatite magma activity. This investigation thus opens new promising areas for Nb and REE prospection in the eastern part of the Amba Dongar carbonatite body.
Gesehen am 24.09.2020